Wakaf Produktif dan Pemberdayaan Masyarakat: Studi Kasus Model Pengentasan Kemiskinan di Yayasan Nurul Hayat - M. Nasyah Agus Saputra; Tri Ardiyanto Aska; Zubaidah Nasution (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2022)
Productive waqf can be an instrument of economic development. Community empowerment in productive waqf is carried out by improving independence in daily activities or a community effort with synergy from social institutions. Nurul Hayat Foundation as a fund management institution and distribution of waqf productively is expected to have the right strategy to build the community economy, especially in the empowerment model carried out by social institutions. This study aims to determine the role of waqf productively in empowering human resources to improve welfare through social institutions, namely the Nurul Hayat Surabaya Foundation. Based on empowerment indicators covering impact, availability, relevance, utilization, coverage, affordability, and efficiency. This research uses qualitative method to productive waqf management based on direct approach from interview, observation, documentation. The results of this study discuss the design of a poverty alleviation model of community empowerment to improve the standard of living and welfare of alaihi  through productive waqf at the Nurul Hayat Foundation, Surabaya.Keywords: Productive Waqf, Empowerment, Poverty Alleviation Model.